Influence Of Production Costs on The Financial Condition of Enterprises - Sattarov Tulkin Abdikhalilovich (Global Scientific Publishing, 2024)
This article investigates the content of traditional factors affecting the financial status of enterprises. It examines important indicators whose magnitude directly impacts the financial stability of corporations. An analytical assessment is provided for each indicator that can significantly influence the overall state of enterprise activities. The document outlines specific techniques for assessing the profitability or efficiency of firms, considering the prevailing circumstances, and proposes definite strategies for upcoming periods based on the financial metrics of these organizations.
Keywords: financial status; loss; income; profit